2004
DOI: 10.1080/01443610400009758
|View full text |Cite
|
Sign up to set email alerts
|

Tubal endometriosis mimicking an ectopic pregnancy

Abstract: It was fortunate that the woman could recognise that she had expelled only a part of the IUCD. If she had missed it she could have had various complications. The transverse limb of the coil could have entered the fallopian tube and caused a tubal perforation. This type of perforation would be possible in a single horizontal smooth arm IUCD (nova T type) and the horizontal arm of the broken IUCD would behave in the same manner. This would also have left the surgeon in a dilemma as to where the vertical limb of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A total of 13 studies were finally considered eligible for inclusion [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Among them, four were observational, which included a total of 633 patients and mainly focused on the prevalence of tubal EM among patients with various gynecological diseases, as well as on disease-related characteristics and histopathology [ 16 , 17 , 18 , 19 ], while two studies focused on analyzing the genetic profile of patients with tubal EM [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13 studies were finally considered eligible for inclusion [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Among them, four were observational, which included a total of 633 patients and mainly focused on the prevalence of tubal EM among patients with various gynecological diseases, as well as on disease-related characteristics and histopathology [ 16 , 17 , 18 , 19 ], while two studies focused on analyzing the genetic profile of patients with tubal EM [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, four were observational, which included a total of 633 patients and mainly focused on the prevalence of tubal EM among patients with various gynecological diseases, as well as on disease-related characteristics and histopathology [ 16 , 17 , 18 , 19 ], while two studies focused on analyzing the genetic profile of patients with tubal EM [ 20 , 21 ]. The remaining seven studies were case reports [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The main patient and disease characteristics of the included observational studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in some cases a preoperative differential diagnosis with other pelvic diseases such as pyelonephritis, ectopic pregnancy, pelvic inflammatory disease, and hydrosalpinx was difficult. 13,15,17 An accurate preoperative work-up is necessary to locate endometriotic lesions and to ensure a complete surgical removal. The poor predictive value of the pelvic examination was demonstrated in a study conducted by Nezhat et al 18 regarding 91 patients with surgically confirmed endometriosis, of whom 47% had a normal bimanual examination.…”
Section: Discussionmentioning
confidence: 99%